GAME ONLINE DI KECAMATAN BAJENG KABUPATEN GOWA - H, Mursalim; Kasjim Salenda; Hamza Hasan; Mera, Nasaruddin (ISTIQRA: Jurnal Hasil Penelitian, 2023)
The development of the industrial world is in line with technological developments which present an online game application that can be downloaded and installed easily on a smartphone or Android mobile phone to be played, online game application in question is Higgs domino island. To enjoy the game, players are required to have chips or money. Meanwhile, the chips or money that players have are not guaranteed to increase or decrease when playing the game. Because luck is the only chance in the game. So the practice of playing Higgs domino island is very similar to gambling games in general. Therefore, this study aims to find out and explain the review of Islamic criminal law on the highs domino island game. researchers used qualitative methods. Data collection in the study began with documentation, observation, and interviews from the data that had been collected by the researcher then analyzed it using triangulation techniques resulting in the conclusion that the online game Higgs Domino Islam in the review of Islamic criminal law contains elements of maysir, while for formal elements or pillars of syar' I gambling offenses can be seen in the Al-Qur'an Surah Al-Maidah verses 90 to 91. From this explanation, it is hoped that elements of the police and government will be involved . community leaders, religious leaders, and youth leaders can work together to make people aware in Bajeng District, Gowa Regency that the Higgs domino island game has similarities with the elements of the crime of gambling